Ezhi-Nisidotamang Ininaatigoog Miinawaa Anishinaabeg Maamawibimaadiziyang (a Cultural, Ethnographic and Scientific Framework for Understanding Maple and Human Relations) - Breu, Nathon (UWM Digital Commons, 2023)
Ininaatigoog, Acer saccharum, or sugar maple trees have been around 66 million yearsproviding sustenance for thousands of years for those who utilize it1 . They provide food and shelter, supplying necessary provisions for all. For Indigenous people when ininaatigoog sap starts to run, it is a sign of springtime, a celebration of life. In Spring the Anishinaabeg, specifically the Ojibwe, Potawatomi, and Odawa, go to their sugar camps, and start the rigorous process of harvesting the sap. In the past the Anishinaabeg moved from their winter camps into their spring sugar camps to transform the sap into maple sugar. Stories are told, and families enjoy mino-bimaadiziwin, the good life. This dissertation examines the relationship between sugar maples and humans, while examining multiple ways of communicating within a shared biome to provide a framework for integrating the experiences, messages, and knowledge of all members of the community. This framework allows all beings to have equal agency as they face the challenges of living within and stewarding their environment as climate change accelerates. This framework integrates contemporary global scientific practices, and Anishinaabe scientific traditions of observation - naanagadawaabandan (seeing data and things in the world), naanaagadawaabam (seeing living relationships). I focus on ininaatigoog and Anishinaabeg, 1 Bruce H.Tiffney, and Steven R. Manchester, “The Use of Geological and Paleontological Evidence in Evaluating Plant Phylogeographic Hypotheses in the Northern Hemisphere Tertiary,” International Journal of Plant Sciences 162, no. S6 (2001): S3–17. https://doi.org/10.1086/323880 (accessed July 15, 2022). iii looking at their history, culture, and the integrated idea of naanagadawaabandan combined with naanagadawaabam of the ininaatigoog as an example of how to utilize this framework. To accurately represent the ininaatigoog, and the Anishinaabeg, and the specific relationships of practitioners in this biome, I have used Ojibwemowin throughout the text. ...